THE STUDENTS’ PERCEPTION ON SUMMARY WRITING AS A WAY TO LEARN GRAMMAR - Rany Maltha Aida (Journal of English and Education, 2014)
The study is entitled the students’ perception on summary writing as a way to learn grammar. It is aimed to investigate the students’ opinion on summary writing as a way to learn grammar and their obstacles in the implementation. The data for this study were gained through qualitative method that used questionnaire and interview, and the respondents were first semester students who used summary writing as their learning activity. The study reveals that the students have positive perception on the use of summary writing, they were interested in the subject and give positive perceptions because the students agreed that the subject and summary writing gave so much knowledge and information that will be beneficial for them in the future. Meanwhile, it is also shown that students face some difficulties in writing the summary, such as difficult in understanding resource text, having lack of vocabulary, lack of grammar mastery also lack of idea to produce the summary. The result of the study is expected to give contribution in improving EFL teaching and learning activity, especially in learning grammar. Keywords: Students’ Perception, Summary Writing, Learning Grammar